African crop science journal Vol. 2 - - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Integrating the management of pests, weeds and diseases of cassava in Africa African crop science journal Vol. 2 ISSN 1021 9730/94.